One stone two birds: Ce/Fe bimetallic MOF-derived mesoporous carbons for sustainable fluoride assay and scavenging - Nan Sun; Hongxia Deng; Niya Ye; Yang Zhang; Yue Zhang (Journal of Environmental Chemical Engineering, 2026)

Influence of structural stability of meat proteins on intragastric digestion kinetics and gastric emptying - Hongxia Liu; Feifan Zhang; Yang Zhai; Haifeng Li; Jichao Huang; Jingxin Sun; Ming Huang (Food Research International, 2026)

Sustainable mechanochromism and photochromism achieved by incorporating rhodamine into dialdehyde bacterial cellulose - Zheyu Shen; Qiuhao Yi; Bianjing Sun; Yalei Qiao; Xinyu Chen; Chenchen Qin; Lin Shi; Hongxia Qu; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2026)

Harnessing SNPs and InDels from whole-genome sequencing to enhance genomic prediction in sturgeons - Hailiang Song; Wei Wang; Tian Dong; Xiaoyu Yan; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

Development and validation of a 40 K liquid SNP array for the sturgeon - Hailiang Song; Tian Dong; Wei Wang; Xiaoyu Yan; Boyun Jiang; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

MXene-supported nanoscale zero-valent iron for Cu(II)-EDTA decomplexation and copper immobilization: Mechanistic insights and application potential - Yuxuan Zhang; Jun Luo; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Bin Gao (Chemical Engineering Journal, 2026)

Systematic Categorization and Functional Diversity of Secondary Metabolites from Bacillus spp.: A Review - Yihan Lv; Huanxu Sun; Tajin Wang; Xinyue Wang; Haipeng Zhang; Hongxia Ma (Probiotics and Antimicrobial Proteins, 2026)

Influence of polystyrene microplastics on bioconcentration and metabolism of 2-ethylhexyl diphenyl phosphate in common carp (Cyprinus carpio) - Zhihui Zhong; Jingyao Wang; Hongxia Zhao; Jia Zhao; Tadiyose Girma Bekele; Huihui Wan; Yuming Sun; Xintong Li; Xiaonuo Zhang (Journal of Environmental Sciences, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Graphene oxide-modified Ni1.5Mg1.5Al1-LDH/g-C3N4 composites for efficient photocatalytic degradation toward ciprofloxacin - Yonglin Zeng; Qianqian Qin; Hongliang Xu; Shiping Sun; Kehao Zhang; Xiufeng Ren; Bo Song; Mingliang Li; Gang Shao; Hongxia Lu; Hailong Wang (Environmental Research, 2026)

Magneto-piezoelectric synergy in anisotropic short-fiber microspheres: A non-invasive platform for accelerated cutaneous nerve regeneration and wound healing - Yaqiong Liu; Yuqing Shang; Mingzhu Jia; Hongxia Gao; Huoyun Shen; Lele Wang; Chunsheng Xiao; Xinhua Liu; Junjie Sun; Aihua Shi; Jianhong Shen; Haitao Guan; et al. (Chemical Engineering Journal, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Dual-functional silica nanospheres integrating heteropolyacid and sulfonic acid for energy-efficient regeneration of CO2-captured amine solvents - Zhuangzhuang Zheng; Qiang Sun; Hongxia Gao; Zhiwu Liang (Fuel, 2026)

In vitro digestion and fermentation characteristics of ethanol-extracted low molecular weight ginseng polysaccharide (AGP): Interactions with gut microbiota, metabolite regulation, and immunomodulatory effects - Ying Sun; Shu Wang; Wenying Zhang; Kunpeng Lu; Yunxiang Que; Changjiao Zhong; Chengguang He; Haipeng Zhang; Hongxia Ma; Lili Guan (Food Research International, 2026)

Optimizing genomic mating in sturgeon by incorporating dominance effects from whole-genome sequencing - Hailiang Song; Tian Dong; Wei Wang; Xiaoyu Yan; Chenfan Geng; Ai Sun; Song Bai; Hongxia Hu (Aquaculture, 2026)

Construction of SnO2/Bi2O2CO3 Z-type heterojunction for photocatalytic degradation of humic acid under sunlight - Muxi Zhang; Chenchen Liao; Bin Dong; Wenjie Lin; Yu Chen; Penghui Yao; Xiaojie Sun; Hongxia Zhang (Environmental Research, 2026)

Pocket-based lead optimization strategy for the design of laccase inhibitors as potential antifungal agents - Xiaoming Zhang; Xuebo Zhang; Xingxing Lu; Tengda Sun; Zhengxin Zhou; Huan Xu; Xinling Yang; Hongxia Duan; Xili Liu; ShuJing Yu; Li Zhang; Yun Ling (Pesticide Biochemistry and Physiology, 2026)

Revealing the role of the MaLSF1 gene in fruit starch degradation and its regulatory transcription factors in Musa acuminata - Zhao Zhu; Peiguang Sun; Yueruxin Jin; Zhiqiang Jin; Junmei Sun; Jianhui Wu; Yunen Tu; Xiaowan Hou; Jianbin Zhang; Caihong Jia; Yunke Zheng; Yinhua Chen; et al. (Postharvest Biology and Technology, 2026)

Imidazolium-based deep eutectic solvents with multiple interaction sites for enhanced carbazole separation from anthracene slag - Pu Sun; Cuiping Ye; Lei Tian; Hongxia Fan; Wenying Li (Journal of Hazardous Materials, 2026)

Metabolic adaptations of rice roots to methylmercury: Insights from high and low accumulators - Bingcai Xiong; Xinjian Ma; Shufeng Wang; Pan Guo; Xingyue Sun; Yuanqin Gao; Hongxia Du; Ming Ma; Dingyong Wang (Food Chemistry, 2026)

Study on dual-path inhibition mechanisms and multiscale structure-activity relationships in CO2 absorption kinetics of 3AP-based water-lean alcohol solutions - Ningbo Yu; Qiang Sun; Minghao Wang; Huiying Liao; Zhiwu Liang; Hongxia Gao (Chemical Engineering Journal, 2026)

Valorization of Flammulina velutipes residue into a feed additive via co-fermentation to control Escherichia coli - Fengxiang Liang; Changjiao Zhong; Hongbo Shen; Kunpeng Lu; Xingrui Liu; Yajing Bai; Wenqi Liu; Ying Sun; Hongxia Ma; Lili Guan (Bioresource Technology, 2026)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

MAZ-mediated LAMA5 transcription activation promotes gastric cancer progression through the STAT3 signaling - Yu Wang; Jiazhong Xu; Hongxia Zhang; Xiaobo Guo; Hongjun Liu; Qinhui Sun (Functional & Integrative Genomics, 2025)

Association of urinary phthalate metabolites and polycystic ovary syndrome in women undergoing in vitro fertilization - Wenjie Zhou; Shuifang Lei; Hong Lv; Yangqian Jiang; Tianyu Sun; Yanjie Zhang; Hongxia Ma; Jie Wu; Yuan Lin (Reproductive Toxicology, 2025)

Tuning ligand substituents of metal-organic frameworks enhances laccase-like activity for pesticide detection - Zheng Liu; Yufan Feng; Yongxi Cui; Yumeng Wang; Zhuoyan Fu; Jianwei Zhao; Hongxia Li; Chunyan Sun (Food Chemistry, 2025)

Liquiritin and L-Dopa mitigate gaseous elemental mercury toxicity in Tillandsia usneoides: Insights into metabolic reprogramming and phytoremediation potential - Yuanqin Gao; Bingcai Xiong; Xiaoyu Huang; Xingyue Sun; Hongxia Du; Ming Ma (Journal of Hazardous Materials, 2025)

A portable strip sensing platform based on bimetal-organic framework nanozyme for freshness assessment of aquatic products - Zheng Liu; Yufan Feng; Yongxi Cui; Yumeng Wang; Zhuoyan Fu; Hongxia Li; Chunyan Sun (Food Control, 2025)

Smart eutectogel with antibacterial activity for efficiently treating multidrug resistant infection, real-time monitoring and diabetic wound repair - Zijie Wang; Baiwen Qi; Ruizi Wang; Ze Chen; Jingming Zhong; Zheng Wang; Qingfeng Sun; Aixi Yu; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Effects of feeding Aspergillus oryzae on intestinal and fecal methane emissions, and performance of simmental crossbred steers - Hongrui Zhang; Kaijia Sun; Tong Fu; Liyang Zhang; Hongxia Lian; Gaiying Li; Tengyun Gao (Tropical Animal Health and Production, 2025)

Empagliflozin Inhibits Neuronal Ferroptosis Induced by Oxygen–Glucose Deprivation/Reoxygenation by Activating the Nrf2/HO-1 Pathway - Jialiang Ma; Hongxia Wang; Juan Jia; Ting Tao; Lingzhi Shan; Shougang Sun; Manxia Wang (Molecular Neurobiology, 2025)

A versatile biosensor for detecting Zn2 + and Cu2+ in Alzheimer's disease cells and acidic foods via RNA G-quadruplex hydrolysis - Dawei Yang; Hongxia Sun; Ranran Sun; Haoyuan Feng; Ruiyang Bai; Qian Li; Li Yao; Yalin Tang (Journal of Hazardous Materials, 2025)

Facile synthesis of MgAl-LDH/g-C3N4 composites for the photocatalytic degradation toward ciprofloxacin - Qianqian Qin; Hongliang Xu; Shiping Sun; Zhiyuan Zhao; Xiufeng Ren; Mingliang Li; Bo Song; Gang Shao; Hailong Wang; Hongxia Lu (Journal of Environmental Chemical Engineering, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

A machine learning approach fusing multisource spectral data for prediction of floral origins and taste components of Apis cerana honey - Zhaolong Liu; Hongxia Li; Nan Liu; Cuiling Liu; Xiaorong Sun; Lanzhen Chen (Food Research International, 2025)

Cobalt MOF-hybridized nanozyme catalysts breaking pH limitations for boosted chlorpyrifos sensing performance - Ruiqi Zou; Junxiao Shi; Qi Lu; Chunyan Sun; Haiqing Ye; Xu Yan; Fangjie Tian; Hongxia Li (Food Chemistry, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

In situ non-invasive electrical stimulation by magnetically-actuated piezoelectric Fe3O4/PVDF alignment scaffolds for synergistically promoting long-distance peripheral nerve regeneration - Linliang Wu; Yaqiong Liu; Hongxia Gao; Wenchao Guan; Shaolan Sun; Hong Liu; Xuefeng Chu; Guicai Li (Chemical Engineering Journal, 2025)

Construction of synthetic microbial community for pyrazines metabolism in sauce-flavor Baijiu - Xueshan Wang; Guizhen Liu; Yenan Chen; Weijie Dong; Zhongrui Su; Minwan Liu; Na Xu; Xinli Song; Hui Lv; Xiaohui Feng; Zhongguan Sun; Wei Tan; et al. (Systems Microbiology and Biomanufacturing, 2025)

Teratogenic effect evaluation of Monascus red oral exposure to pregnant rats and their gut microbiota - Yuenan Wang; Xuedan Xu; Yun Liu; Zhenfeng Huang; Hongxia Wang; Kexin Wang; Yayi Huang; Xinyu Yang; Tingting Sun; Jieling Wang; Jianbin Tan; Xingfen Yang; et al. (Reproductive Toxicology, 2025)

Synergism of 2′-FL and Lactobacillus plantarum 1.0642 on gut microbiome diversity and functionality in constipated mice: A metagenomic analysis - Nianxu Dou; Chuanqiang Sun; Yongchen Liu; Gaoyun Wu; Hongxia Feng; Yunhe Chang; Shanshan Qian; Juncai Hou (Food Bioscience, 2025)

Transcription factor PdMYB118 in poplar regulates lignin deposition and xylem differentiation in addition to anthocyanin synthesis through suppressing the expression of PagKNAT2/6b gene - Shuo Song; Wei Guo; Yu Guo; Erkun Chao; Sujie Sun; Lizi Zhao; Yanqiu Zhao; Hongxia Zhang (Plant Science, 2025)

Detrital zircon provenance record of the northern shelf in the Rakhine Basin, Bay of Bengal - Liangbo Ding; Hongxia Ma; Guozhang Fan; Xiaoyong Xu; Hongping Wang; Guoping Zuo; Ying Zhang; Hui Sun; Jianan Wu; Junmin Jia; Ming Su; Ce Wang (Marine and Petroleum Geology, 2025)

A novel Ag/Bi/Bi2O2CO3 photocatalyst effectively removes antibiotic-resistant bacteria and tetracycline from water under visible light irradiation - Suo Wang; Changyu Li; Huanshun Yin; Bin Gao; Zhengkun Yu; Yunlei Zhou; Jun Wang; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Environmental Research, 2025)

Antioxidant response fail to rescue growth of Hermetia illucens L. larvae induced by copper accumulated during long-term exposure - Huijie Zhang; Hongxia Sun; Lin Liu; Ye Liao; Yanxin Lu; Qiang Xia (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Environmental applications and toxicity of ionic liquids - Xiuyan Wang; Xin Hu; Dunhan Zhang; Yuxuan Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Journal of Environmental Chemical Engineering, 2024)

Carbon dots-based stimuli-responsive hydrogel for in-situ detection of thiram on fruits and vegetables - Hongxia Li; Yanan Hu; Zhen Lin; Xu Yan; Chunyan Sun; Dong Yao (Food Chemistry, 2024)

Schisandrin A alleviates non-alcoholic fatty liver disease by improving liver metabolic disorders and suppressing the GSK3β signaling pathway - Li Zong; Rui Xu; Yunxia Sun; Junjie Qiu; Huihui Tao; Chengyu Shentu; Hongxia Niu; Tengfei Xu; Yuan Zhou (Food Bioscience, 2024)

High-capacity adsorption of organic dyes using separable pullulan gel encapsulated with PDA-modified ZIF-8 - Ting Su; Hongxia Shang; Xinru Su; Zhixian Sun; Yuehan Li; Linwen Li; Zhen Zhang; Renyong Geng; Shuisheng Chen (Carbohydrate Polymers, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

A recombinant pseudorabies virus surface - displaying the classical swine fever E2 protein induces specific antibodies rapidly - Xinyu Zhang; Hongxia Wu; Tianqi Gao; Yongfeng Li; Dailang Zhong; Mingzhi Li; Shuwen Li; Caoyuan Ma; Assad Moon; Qiang Fu; Hua-Ji Qiu; Yuan Sun (Veterinary Microbiology, 2024)

Photoresponse of Ti3C2Tx MXene promotes its adsorptive-reductive removal of Cr(VI) from water - Yuxuan Zhang; Jun Luo; Xiuyan Wang; Dunhan Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Bin Gao; Hongqiang Ren (Journal of Environmental Management, 2024)

Reclaiming selenium from water using aluminum-modified biochar: Adsorption behaviors, mechanisms, and effects on growth of wheat seedlings - Xiuyan Wang; Tianxiao Li; Xin Hu; Yuxuan Zhang; Dunhan Zhang; Hanshuo Zhang; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Jun Luo; Bin Gao (Environmental Pollution, 2024)

A supramolecular fluorescence probe that simultaneously responds to viscosity and G-quadruplex for autophagy detection - Ruiyang Bai; Dawei Yang; Ranran Sun; Xiufeng Zhang; Lei Shi; Jing Liu; Hongxia Sun; Li Yao; Yalin Tang (Analytica Chimica Acta, 2024)

Modulating the stability and gastrointestinal tolerance of lycopene in low-oil gelatin emulsions by constructing cellulose network barrier - Xin Feng; Hankun Zhu; Hongjie Dai; Yong Yu; Hongxia Tan; Mi Tang; Kangting Sun; Yapeng Lu; Yugang Liu; Liang Ma; Yuhao Zhang (Food Hydrocolloids, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Retraction Note: Green economic revival acquisition: evaluating impact of digital finance and natural resource development - HongXia Sun; DingHe Hu; Xu Zhang (Environmental Science and Pollution Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Functional regulation of microRNA-184 in the replication and infection of Autographa californica multiple nucleopolyhedrovirus - Jin Li; Zhongcui Kang; Hongxia Xu; Shaobin Li; Guopan Li; Xiulian Sun; Chengfeng Lei; Ying Chen (Pesticide Biochemistry and Physiology, 2024)

Travertine deposition rather than tourism activity is the primary contributor to the microplastic risks in alpine karst lakes - Hanyong Zeng; Yijin Wang; Zhen Zhao; Dalin Zhu; Hongxia Xia; Yihua Wei; Peigang Kuang; Dejun An; Ke Chen; Ruilong Li; Yanbao Lei; Geng Sun (Journal of Hazardous Materials, 2024)

Three-year field study on the temporal response of soil microbial communities and functions to PFOA exposure - Hai Huang; Xueyan Lyu; Feng Xiao; Jiaju Fu; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Journal of Hazardous Materials, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

Anisotropic topological scaffolds synergizing non-invasive wireless magnetic stimulation for accelerating long-distance peripheral nerve regeneration - Qi Han; Wenchao Guan; Shaolan Sun; Tiantian Zheng; Linliang Wu; Hongxia Gao; Yaqiong Liu; Yumin Yang; Guicai Li (Chemical Engineering Journal, 2024)

Biocrusts enhance soil nitrogen mineralization and nitrification under experimental warming in a dryland ecosystem - Rui Hu; Hongxia Zhang; Jingyao Sun; Yafeng Zhang; Mingzhu He; Zhishan Zhang (Applied Soil Ecology, 2024)

Combining different ionic polysaccharides and pH treatment improved functional properties of soybean protein amyloid fibrils through structural modifications - Jianling Feng; Shi Liu; Na Sun; Hongxia Dong; Liming Miao; Huan Wang; Xiaohong Tong; Lianzhou Jiang (Food Hydrocolloids, 2024)

Bimetallic PtZn nanoparticles anchored in high-silica SSZ-13 zeolite for efficient propane dehydrogenation - Liancheng Bing; Zan Sun; Shuaiguo Zhang; Baoyu Chen; Hongxia Zhang; Min Wang; Changqing Chu; Dezhi Han; Jiankang Zhang; Fang Wang; Guangjian Wang (Chemical Engineering Journal, 2024)

Genome-wide characterization of Remorin gene family and their responsive expression to abiotic stresses and plant hormone in Brassica napus - Nan Sun; Jiale Zhou; Yanfeng Liu; Dong Li; Xin Xu; Zihao Zhu; Xuesheng Xu; Renhui Zhan; Hongxia Zhang; Limin Wang (Plant Cell Reports, 2024)

The hydrologic nature of swales uncovers remarkable influence of non-topographic factors on catchment-scale soil moisture variation - Yaling Zhang; Yanjia Jiang; Xiangyang Sun; Hongxia Li; Chuan Yuan; Hu Liu; Jinzhao Liu; Carlos R. Mello; Elizabeth W. Boyer; Li Guo (Journal of Hydrology, 2024)

Self-ratiometric fluorescent platform based on upconversion nanoparticles for on-site detection of chlorpyrifos - Xu Zhao; Yang Lu; Bai Li; Minghui Kong; Yanfeng Sun; Hongxia Li; Xiaomin Liu; Geyu Lu (Food Chemistry, 2024)

Effects of Hydrophobic Biochar-Modified Landfill Soil Cover on Methane Oxidation - Qiuhong Li; Meiyan Xing; Bin Dong; Xiaojie Sun; Hongxia Zhang; Xueshuang Lu; Beibei Wu; Hongxiang Zhu (Environmental Management, 2024)

A Novel Zn(II) Coordination Polymer: Fluorescence Performances, Molecular Docking and Loaded with Bleomycin-Hydrogels on Hemangiomas - Shengquan Wang; Lei Sun; Hongxia Gao; Wenpei Zhang (Journal of Fluorescence, 2024)

Degradation and mechanism of PFOA by peroxymonosulfate activated by nitrogen-doped carbon foam-anchored nZVI in aqueous solutions - Changyu Li; Cong Shen; Bin Gao; Wenxu Liang; Yifan Zhu; Weijie Shi; Shiyun Ai; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Chemosphere, 2024)

Exploring the function of MaPHO1 in starch degradation and its protein interactions in postharvest banana fruits - Hongxia Miao; Peiguang Sun; Weina Zhu; Qing Liu; Jianbin Zhang; Caihong Jia; Junmei Sun; Zhao Zhu; Jianghui Xie; Wei Wang; Weiwei Tie; Xinguo Li; et al. (Postharvest Biology and Technology, 2024)

Brain white matter microstructural alterations in patients with systemic lupus erythematosus: an automated fiber quantification study - Peng Zhang; Yanhong Feng; Tianye Xu; Yifan LI; Jianguo Xia; Hongxia Zhang; Zhongru Sun; Weizhong Tian; Ji Zhang (Brain Imaging and Behavior, 2024)

Selenium Protects Yellow Catfish (Tachysurus fulvidraco) from Low-Temperature Damage via the Perspective Analysis of Metabolomics and Intestinal Microbes - Junru Hu; Lei Wang; Guoxia Wang; Hongxia Zhao; Huijie Lu; Kai Peng; Wen Huang; Zhenxing Liu; Ding Liu; Yuping Sun (Fishes, 2024)
The effects of selenium supplementation in Tachysurus fulvidraco (T. fulvidraco) on low-temperature stress are not known. In this study, 280 healthy T. fulvidraco were divided into two groups, the G0 group (a control group) and the T0 group (a selenium treatment group on a 0.22 mg/kg diet), for a 6-week feeding time. Then, low-temperature stress (water temperature dropped from 26 to 13 °C, with a rate of 1 °C/h) was administered after that. The feeding results showed that selenium increased the percent weight gain (PWG), specific growth rate (SGR), and survival rate (SR) of T. fulvidraco and decreased the feed conversion rate (FCR), but these differences were not significant (p > 0.05). Under low temperatures, selenium still has no significant effects on antioxidant indexes such as glutathione peroxidase (GSH-Px) activity, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content in serum (p > 0.05). However, metabolomic analysis revealed that selenium caused changes in lipids and lipid-like molles, organic acids and their derivatives, and fatty acyls. Choline, linoleic acid, and glycerophospholipid metabolism pathways; d-arginine and d-ornithine metabolism; valine, leucine, and isoleucine degradation; and biosynthesis pathways, as well as pyrimidine metabolism pathways, were activated to produce these metabolites to combat against this stress. In addition, selenium increased the diversity of intestinal microbes in T. fulvidraco and decreased the relative abundance of Plesiomonas. However, the combined analysis showed the intestinal microbe changes did not affect metabolite production. In summary, selenium activated lipid, carbohydrate, and amino acid metabolism for energy substance provision, reduced the oxidation and production of other harmful substances, and increased the intestinal microbe diversity of T. fulvidraco to improve resistance to low-temperature stress.

Dual-responsive fluorescence probe for measuring HSO3− and viscosity and its application in living cells and real foods - Xiaoying Ma; Xiufeng Zhang; Buyue Zhang; Dawei Yang; Hongxia Sun; Yalin Tang; Lei Shi (Food Chemistry, 2024)

Dietary supplementation with American ginseng dietary fiber ameliorates intestinal mucosal barrier injury in immunosuppressed mice - Jiyue Sha; Zhengbo Liu; Hongxia Yu; Xiaohui Huo; Jiajia Wang; Yuanyuan Duan; Wei Li; Di Qu; Zhiman Li; Jianbo Chen; Xueqing Li; Yinshi Sun (Food Bioscience, 2023)

The bioaccumulation and biotransformation of tetrabromobisphenol A bis (allyl ether) in common carp (Cyprinus carpio) - Jia Zhao; Hongxia Zhao; Zhihui Zhong; Tadiyose Girma Bekele; Huihui Wan; Yuming Sun; Xintong Li; Xiaonuo Zhang; Zhansheng Li (Environmental Science and Pollution Research, 2023)

Residue behaviors, degradation, processing factors, and risk assessment of pesticides in citrus from field to product processing - Hongxia Tang; Qiang Sun; Jiaqing Huang; Guangyue Wen; Lijun Han; Lei Wang; Ying Zhang; Maofeng Dong; Weimin Wang (Science of The Total Environment, 2023)

Cooperative emission reduction behaviour of supply chain enterprises under cap-and-trade and government subsidies - Hongxia Sun; Kexin Wang; Xinjian Du (Environment, Development and Sustainability, 2023)

Zeolitic imidazolate framework/aptamer-based fluorescence assay for the facile and high-sensitivity detection of acetamiprid - Hongxia Li; Changshun Su; Ni Liu; Qi Lu; Ningxin Zhang; Chunyan Sun; Xu Yan (Analytica Chimica Acta, 2023)

RETRACTED ARTICLE: Green economic revival acquisition: evaluating impact of digital finance and natural resource development - HongXia Sun; DingHe Hu; Xu Zhang (Environmental Science and Pollution Research, 2023)

Vitamin B ameliorates PM2.5-induced kidney damage by reducing endoplasmic reticulum stress and oxidative stress in pregnant mice and HK-2 - Chunming Xu; Qian Zhang; Guochen Huang; Jia Huang; Xiaoyan Fu; Meifang Liu; Yonghong Sun; Hongxia Zhang (Toxicology, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Enhanced CO2 desorption rate for rich amine solution regeneration over hierarchical HZSM-5 catalyst - Qiang Sun; Hongxia Gao; Teerawat Sema; Zhiwu Liang (Chemical Engineering Journal, 2023)

Effect of oil phases on the stability of myofibrillar protein microgel particles stabilized Pickering emulsions: The leading role of viscosity - Xin Feng; Yi Sun; Hongxia Tan; Liang Ma; Hongjie Dai; Yuhao Zhang (Food Chemistry, 2023)

Gold nanoclusters-manganese dioxide composite-based fluorescence immunoassay for sensitive monitoring of fenitrothion degradation in Chinese cabbage - Ting Lv; Boxu Wang; Ningyi Xu; Baitong Shang; Ni Liu; Changshun Su; Chuanyu Yang; Hongxia Li; Zhenlin Xu; Chunyan Sun (Food Chemistry, 2023)

Hollow self-floating microspheres capture cobalt (Co2+)/nickel (Ni2+) ions from the acidic leachate of spent lithium-ion battery cathodes - Tuo Wang; Yanyan An; Junxia Sun; Hongxia Yang; Yaoyao Huang; Huaili Zheng (Chemical Engineering Journal, 2023)

Use of stacked Gaussian processes regression method to improve prediction of groundwater solute transport model - Yue Pan; Xiankui Zeng; Hongxia Xu; Yuanyuan Sun; Dong Wang; Jichun Wu (Journal of Hydrology, 2023)

Myofibrillar protein microgels stabilized high internal phase Pickering emulsions with heat-promoted stability - Hongjie Dai; Yi Sun; Xin Feng; Liang Ma; Hai Chen; Yu Fu; Hongxia Wang; Yuhao Zhang (Food Hydrocolloids, 2023)

Characterization of RING-type ubiquitin SINA E3 ligases and their responsive expression to salt and osmotic stresses in Brassica napus - Fengyan Fang; Wenlong Zhou; Yanfeng Liu; Zhizhong Song; Songfeng Zheng; Fei Wang; Zeyu Lu; Dazhuang Qi; Bei Li; Nan Sun; Xiaoli Tang; Juan Zhang; et al. (Plant Cell Reports, 2023)

Gut Microbiota in Children with Hand Foot and Mouth Disease on 16S rRNA Gene Sequencing - Yan Zhuang; Yiyan Lin; Hongxia Sun; Zaiting Zhang; Tao Wang; Rongjun Fan; Lu Han (Current Microbiology, 2023)

pH-responsive chitosan-based film containing oregano essential oil and black rice bran anthocyanin for preserving pork and monitoring freshness - Yuanpeng Hao; Jiamu Kang; Xiaoqi Guo; Meiyu Sun; Hui Li; Hongtong Bai; Hongxia Cui; Lei Shi (Food Chemistry, 2023)

Granular limestone amended sand filters for enhanced removal of nanoplastics from water: Performance and mechanisms - Xiaohui Li; Yuanyuan Zhang; Hongxia Xu; Yuanyuan Sun; Bin Gao; Jichun Wu (Water Research, 2023)

Effects of biofilms on the retention and transport of PFOA in saturated porous media - Jiaju Fu; Bin Gao; Hongxia Xu; Shefeng Hao; Jinghua Ren; Jichun Wu; Yuanyuan Sun (Journal of Hazardous Materials, 2023)

Graphitic carbon nitride-based photocatalysts in the applications of environmental catalysis - Hongxia Lin; Jinmo Wu; Fan Zhou; Xiaolong Zhao; Pengfei Lu; Guanghui Sun; Yuhan Song; Yayun Li; Xiaoyong Liu; Hongxing Dai (Journal of Environmental Sciences, 2023)

Laser-induced graphene (LIG)-based Au@CuO/V2CTx MXene non-enzymatic electrochemical sensors for the urine glucose test - Feiyun Cui; Haiming Sun; Xueqiong Yang; Hang Zhou; Yiqi Wu; Jing Li; Hongxia Li; Jianlei Liu; Chijia Zeng; Bin Qu; Jufan Zhang; Qin Zhou (Chemical Engineering Journal, 2023)

Genomic selection and its research progress in aquaculture breeding - Hailiang Song; Tian Dong; Xiaoyu Yan; Wei Wang; Zhaohui Tian; Ai Sun; Ying Dong; Hua Zhu; Hongxia Hu (Reviews in Aquaculture, 2023)
Since its introduction in 2001, genomic selection (GS) has progressed rapidly. As a research and application hot topic, GS has led to a revolution in the field of animal and plant breeding. Thanks to its ability to overcome the shortcomings of traditional breeding methods, GS has garnered increasing attention. Both theoretical and practical breeding studies have revealed the higher accuracy of GS than that of traditional breeding, which can accelerate genetic gain. In recent years, many GS studies have been conducted on aquaculture species, which have shown that GS produces higher prediction accuracy than traditional pedigree‐based method. The present study reviews the principles and processes, preconditions, advantages, analytical methods and factors influencing GS as well as the progress of research in aquaculture into these aspects. Furthermore, future directions of GS in aquaculture are also discussed, which should expand its application to more aquaculture species.

Effect of ventilation quantity on electron transfer capacity and spectral characteristics of humic substances during sludge composting - Zhihan Tan; Hongxiang Zhu; Xiaosong He; Beidou Xi; Yuxin Tian; Xiaojie Sun; Hongxia Zhang; Quanyi Ouche (Environmental Science and Pollution Research, 2022)

Menin regulates lipid deposition in mouse hepatocytes via interacting with transcription factor FoxO1 - Shengxuan Wang; Tingjun Liu; Lili Sun; Hongxia Du; Zhongjin Xu; Ranran Li; Ying Yu; Yongjiang Mao; Kerong Shi (Molecular and Cellular Biochemistry, 2022)

Erratum to: A buried submarine canyon in the northwest South China Sea: architecture, development processes and implications for hydrocarbon exploration - Bin Wang; Fuliang Lyu; Shuang Li; Jian Li; Zhili Yang; Li Li; Xuefeng Wang; Yintao Lu; Taotao Yang; Jingwu Wu; Guozhong Sun; Hongxia Ma; et al. (Acta Oceanologica Sinica, 2022)

Divergent Molecular and Physiological Response of Two Maize Breeding Lines Under Phosphate Deficiency - Yanling Sun; Hongxia Zheng (Plant Molecular Biology Reporter, 2022)
Inorganic phosphate (Pi) deficiency is a main limiting factor on crops growth and to select low-Pi tolerant breeding lines is very significant for crop breeding. Here, two contrasting maize ( Zea mays L.) breeding lines showed different physiological response to Pi deficiency. The low-Pi tolerant QXN233 maintained normal growth, including high fresh weight, green leaves, strong shoots, and numerous roots relative to that of the sensitive MH05-4, mainly due to QXN233’ high Pi content in shoots under Pi deficiency. Importantly, some Pi-responsive genes were detected, and among them, Pi transporters ZmPHT1;1 and ZmPHT1;9 as well as phytase gene Zmphytase 2 were expressed increasingly in QXN233 compared to MH05-4 under Pi deprivation or Pi resupply. Moreover, QXN233 had higher proline content, soluble sugar content, and SOD activity than MH05-4, related with its tolerance. Taken together, this study enriches the understanding of the mechanism of maize responding to Pi deficiency.

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

GmFULa improves soybean yield by enhancing carbon assimilation without altering flowering time or maturity - Yanlei Yue; Shi Sun; Jiawen Li; Haidong Yu; Hongxia Wu; Baiquan Sun; Tao Li; Tianfu Han; Bingjun Jiang (Plant Cell Reports, 2021)
Key message GmFULa improved soybean yield by enhancing carbon assimilation. Meanwhile, different from known yield-related genes, it did not alter flowering time or maturity. Abstract Soybean ( Glycine max (L.) Merr.) is highly demanded by a continuously growing human population. However, increasing soybean yield is a major challenge. FRUITFULL ( FUL ), a MADS-box transcription factor, plays important roles in multiple developmental processes, especially fruit and pod development, which are crucial for soybean yield formation. However, the functions of its homologs in soybean are not clear. Here, through haplotype analysis, we found that one haplotype of the soybean homolog GmFULa ( GmFULa-H02 ) is dominant in cultivated soybeans, suggesting that GmFULa-H02 was highly selected during domestication and varietal improvement of soybean. Interestingly, transgenic overexpression of GmFULa enhanced vegetative growth with more biomass accumulated and ultimately increased the yield but without affecting the plant height or changing the flowering time and maturity, indicating that it enhances the efficiency of dry matter accumulation. It also promoted the yield factors like branch number, pod number and 100-seed weight, which ultimately increased the yield. It increased the palisade tissue cell number and the chlorophyll content to promote photosynthesis and increase the soluble sugar content in leaves and fresh seeds. Furthermore, GmFULa were found to be sublocalized in the nucleus and positively regulate sucrose synthases ( SUSs ) and sucrose transporters ( SUTs ) by binding with the conserved CArG boxes in their promoters. Overall, these results showed GmFULa promotes the capacity of assimilation and the transport of the resultant assimilates to increase yield, and provided insights into the link between GmFULa and sucrose synthesis with transport-related molecular pathways that control seed yield.

Correction to: CYP3A5 and CYP3A7 genetic polymorphisms affect tacrolimus concentration in pediatric patients with nephrotic syndrome - Hongxia Liu; Qinxia Xu; Wenyan Huang; Qi Zhao; Zhihu Jiang; Xinyu Kuang; Zhiling Li; Huajun Sun; Xiaoyan Qiu (European Journal of Clinical Pharmacology, 2021)

Status, Sources, and Health Risk of Hexachlorocyclohexanes in the Air of the Rural Region of Zhangzhou, Southeast China - Wen Sun; Hongxia Liu; Jiaquan Zhang; Baoyun Zhang; Chengkai Qu (Bulletin of Environmental Contamination and Toxicology, 2021)

NEAT1 Decreasing Suppresses Parkinson’s Disease Progression via Acting as miR-1301-3p Sponge - Qiang Sun; Yueliang Zhang; Songlin Wang; Fang Yang; Hongxia Cai; Yu Xing; Zengfeng Chen; Jun Chen (Journal of Molecular Neuroscience, 2021)

A buried submarine canyon in the northwestern South China Sea: architecture, development processes and implications for hydrocarbon exploration - Bin Wang; Fuliang Lü; Shuang Li; Jian Li; Zhili Yang; Li Li; Xuefeng Wang; Yintao Lu; Taotao Yang; Jingwu Wu; Guozhong Sun; Hongxia Ma; et al. (Acta Oceanologica Sinica, 2021)

Genome-wide association study identifies QTL for thousand grain weight in winter wheat under normal- and late-sown stressed environments - Xiaobo Wang; Panfeng Guan; Mingming Xin; Yongfa Wang; Xiyong Chen; Aiju Zhao; Manshuang Liu; Hongxia Li; Mingyi Zhang; Lahu Lu; Jinbo Zhang; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2021)

Isolation and complete genome sequencing of the virulent phage vB_EcoS_XY3 infecting multidrug-resistant Escherichia coli - Pan Fu; Qiang Zhao; Li Shi; Qin Xiong; Hongxia Xu; Senmao Cai; Qianqian Xu; Xiaodong Sun; Ming Sang (Archives of Virology, 2021)

Dorsolateral Striatal proBDNF Improves Reversal Learning by Enhancing Coordination of Neural Activity in Rats - Wei Sun; Hongxia Che; Jia Li; Dongxin Tang; Xiaoyun Liu; Wenhui Liu; Lei An (Molecular Neurobiology, 2020)

Effects of Temperature, Solution pH, and Ball-Milling Modification on the Adsorption of Non-steroidal Anti-inflammatory Drugs onto Biochar - Ran Luo; Xiaohui Li; Hongxia Xu; Yuanyuan Sun; Jichun Wu (Bulletin of Environmental Contamination and Toxicology, 2020)

New Insights on ‘GALA’ Apple Fruit Development: Sugar and Acid Accumulation: A Transcriptomic Approach - Hongxia Tao; Hanqing Sun; Yufei Wang; Xuena Song; Yanping Guo (Journal of Plant Growth Regulation, 2020)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Calcium Ions Turn on the Fluorescence of Oxytetracycline for Sensitive and Selective Detection - Hongxia Chen; Junxiang Peng; Long Yu; Hui Chen; Mingtai Sun; Zhenli Sun; Runyan Ni; Khalid A. Alamry; Hadi M. Marwani; Suhua Wang (Journal of Fluorescence, 2020)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

CYP3A5 and CYP3A7 genetic polymorphisms affect tacrolimus concentration in pediatric patients with nephrotic range proteinuria - Hongxia Liu; Qinxia Xu; Wenyan Huang; Qi Zhao; Zhihu Jiang; Xinyu Kuang; Zhiling Li; Huajun Sun; Xiaoyan Qiu (European Journal of Clinical Pharmacology, 2019)

Urban VOC profiles, possible sources, and its role in ozone formation for a summer campaign over Xi’an, China - Jian Sun; Zhenxing Shen; Yue Zhang; Zhou Zhang; Qian Zhang; Tian Zhang; Xinyi Niu; Yu Huang; Long Cui; Hongmei Xu; Hongxia Liu; Junji Cao; et al. (Environmental Science and Pollution Research, 2019)

Effect of Residual NAPLs on the Transport of Bisphenol A and Bisphenol S in Saturated Porous Media - Yanfeng Shi; Bin Gao; Yuanyuan Sun; Kaixuan Sun; Hongxia Xu; Jichun Wu (Water, Air, & Soil Pollution, 2019)

Effect of cation type in mixed Ca-Na systems on transport of sulfonamide antibiotics in saturated limestone porous media - Kaixuan Sun; Yuanyuan Sun; Bin Gao; Hongxia Xu; Jichun Wu (Environmental Science and Pollution Research, 2019)

Complete genome sequence of an alternavirus from the phytopathogenic fungus Fusarium incarnatum - Xiaoting Zhang; Yuan Xie; Fang Zhang; Hangjun Sun; Yingying Zhai; Songbai Zhang; Hongxia Yuan; Lin Zhou; Fei Gao; Honglian Li (Archives of Virology, 2019)

Importance of Organic Matter to the Retention and Transport of Bisphenol A and Bisphenol S in Saturated Soils - Yanfeng Shi; Yuanyuan Sun; Bin Gao; Hongxia Xu; Jichun Wu (Water, Air, & Soil Pollution, 2019)

Effects of chromium picolinate supplementation on growth, body composition, and biochemical parameters in Nile tilapia Oreochromis niloticus - Hongxia Li; Xiao Meng; Wenju Wan; Hanliang Liu; Minmin Sun; Hongwei Wang; Jiting Wang (Fish Physiology and Biochemistry, 2018)

Porous nano-cerium oxide wood chip biochar composites for aqueous levofloxacin removal and sorption mechanism insights - Shengze Yi; Yuanyuan Sun; Xin Hu; Hongxia Xu; Bin Gao; Jichun Wu (Environmental Science and Pollution Research, 2018)

Retention and Transport of Bisphenol A and Bisphenol S in Saturated Limestone Porous Media - Yanfeng Shi; Yuanyuan Sun; Bin Gao; Hongxia Xu; Xiaoqing Shi; Jichun Wu (Water, Air, & Soil Pollution, 2018)

Mercury methylation in the soils and sediments of Three Gorges Reservoir Region - Ming Ma; Hongxia Du; Dingyong Wang; Tao Sun (Journal of Soils and Sediments, 2018)

Retention and Transport of PAH-Degrading Bacterium Herbaspirillum chlorophenolicum FA1 in Saturated Porous Media Under Various Physicochemical Conditions - Xiaohui Li; Hongxia Xu; Bin Gao; Yuanyuan Sun; Xiaoqing Shi; Jichun Wu (Water, Air, & Soil Pollution, 2017)

Genome-wide identification of SAUR genes in watermelon (Citrullus lanatus) - Na Zhang; Xing Huang; Yaning Bao; Bo Wang; Hongxia Zeng; Weishun Cheng; Mi Tang; Yuhua Li; Jian Ren; Yuhong Sun (Physiology and Molecular Biology of Plants, 2017)

A New Non-Darcy Flow Model for Low-Velocity Multiphase Flow in Tight Reservoirs - Yi Xiong; Jinbiao Yu; Hongxia Sun; Jiangru Yuan; Zhaoqin Huang; Yu-shu Wu (Transport in Porous Media, 2017)

Mercury-methylating genes dsrB and hgcA in soils/sediments of the Three Gorges Reservoir - Hongxia Du; Ming Ma; Tao Sun; Xianzhu Dai; Caiyun Yang; Feng Luo; Dingyong Wang; Yasuo Igarashi (Environmental Science and Pollution Research, 2017)

Can the narrowing of the Lower Yellow River by regulation result in non-siltation and even channel scouring? - Zanying Sun; Wanzhan Wang; Yong Li; Mingwu Zhang; Hongxia Shang; Fangxiu Zhang (Journal of Geographical Sciences, 2016)

In vitro antiviral effect of germacrone on feline calicivirus - Hongxia Wu; Yongxiang Liu; Shaopo Zu; Xue Sun; Chunguo Liu; Dafei Liu; Xiaozhan Zhang; Jin Tian; Liandong Qu (Archives of Virology, 2016)

Biodegradation of Pyrene by Free and Immobilized Cells of Herbaspirillum chlorophenolicum Strain FA1 - Hongxia Xu; Xiaohui Li; Yuanyuan Sun; Xiaoqing Shi; Jichun Wu (Water, Air, & Soil Pollution, 2016)

Influence of flow velocity and spatial heterogeneity on DNAPL migration in porous media: insights from laboratory experiments and numerical modelling - Fei Zheng; Yanwei Gao; Yuanyuan Sun; Xiaoqing Shi; Hongxia Xu; Jichun Wu (Hydrogeology Journal, 2015)

Atmospheric mercury deposition and its contribution of the regional atmospheric transport to mercury pollution at a national forest nature reserve, southwest China - Ming Ma; Dingyong Wang; Hongxia Du; Tao Sun; Zheng Zhao; Shiqing Wei (Environmental Science and Pollution Research, 2015)

Effect of Change of Mechanical Ventilation Position on the Treatment of Neonatal Respiratory Failure - Jiebin Wu; Jingfang Zhai; Hongxia Jiang; Yingjun Sun; Bao Jin; Yanyan Zhang; Bin Zhou (Cell Biochemistry and Biophysics, 2015)

Genetic variations in DROSHA and DICER and survival of advanced non-small cell lung cancer: a two-stage study in Chinese population - Shuangshuang Wu; Yun Pan; Songyu Cao; Jiali Xu; Yan Liang; Yan Wang; Lei Chen; Yunyan Wei; Chongqi Sun; Weihong Zhao; Zhibin Hu; Hongxia Ma; et al. (Genes & Genomics, 2015)

Forest runoff increase mercury output from subtropical forest catchments: an example from an alpine reservoir in a national nature reserve (southwestern China) - Ming Ma; Dingyong Wang; Tao Sun; Zheng Zhao; Hongxia Du (Environmental Science and Pollution Research, 2015)

Effects of Humic Acid and Solution Chemistry on the Retention and Transport of Cerium Dioxide Nanoparticles in Saturated Porous Media - Xueyan Lv; Bin Gao; Yuanyuan Sun; Xiaoqing Shi; Hongxia Xu; Jichun Wu (Water, Air, & Soil Pollution, 2014)

An EGFR gene of the Pacific oyster Crassostrea gigas functions in wound healing and promotes cell proliferation - Lingling Sun; Pin Huan; Hongxia Wang; Fengsong Liu; Baozhong Liu (Molecular Biology Reports, 2014)

A TFIIIA-type zinc finger protein confers multiple abiotic stress tolerances in transgenic rice (Oryza sativa L.) - Ji Huang; Shujing Sun; Dongqing Xu; Hongxia Lan; Hui Sun; Zhoufei Wang; Yongmei Bao; Jianfei Wang; Haijuan Tang; Hongsheng Zhang (Plant Molecular Biology, 2012)

Endocrine-disrupting equivalents in industrial effluents discharged into Yangtze River - Wei Shi; Xiaoyi Wang; Wei Hu; Hong Sun; Ouxi Shen; Hongling Liu; Xinru Wang; John P. Giesy; Shupei Cheng; Hongxia Yu (Ecotoxicology, 2009)

Changes Of Hydrological Environment And Their Influences On Coastal Wetlands InThe Southern Laizhou Bay, China - Xuliang Zhang; Yuanzhi Zhang; Hongxia Sun; Dongxing Xia (Environmental Monitoring and Assessment, 2006)